Local Support Practices Contribute into Strengthening Entrepreneurs Capacity: Enterprise Resilience - Chongbang, Nirmal; Bhandari, Manoj (International Journal of Indonesian Business Review, 2024)
The pandemic severely affected local and small enterprises. During the lockdown, local entrepreneurs suffered due to low earnings and savings, weak informal support practices, inadequate risk transfer measures, and insufficient state recovery policies and budgets. This paper investigates the primary self-supporting practices of entrepreneurs during the pandemic, assesses how available informal support contributed to building resilience, and examines how local entrepreneurs sustained themselves during the crisis. It explores whether local practices such as self-saving, community support, and state assistance were adequate for resilience building. The study employed convenience sampling of over forty-one micro, small, and medium entrepreneurs across various districts in Nepal. Research methods included closed-ended questionnaires, phone interviews, and in-person discussions. Data analysis involved qualitative and quantitative methods, revealing that self-saving was crucial for resilience, followed by risk transfer practices. The study concludes that local self-saving capacities, coupled with community support, significantly enhance resilience among entrepreneurs. However, informal support practices and state policies for pandemic recovery fell short of expectations.